Profil Literasi lingkungan siswa kelas X di SMKN 1 Ampelgading - Azizah, Nur; Roshayanti, Fenny (Jurnal Inovasi Pembelajaran di Sekolah, 2024)
This research aims to determine the environmental literacy profile of class X students at SMKN 1 Ampelgading. This research is a qualitative descriptive research with a survey method. The population in this study was class X at SMKN Ampelgading, totaling 20 classes with a sample of 143 students taken from 4 classes at SMKN 1 Ampelgading. Sampling used the Proportionate Random Sampling technique. Data collection techniques use questionnaires and written tests. The research results show that in general the environmental literacy level of class X students at SMKN 1 Ampelgading is classified as low with an average percentage of 40%. It is known that the highest level of environmental literacy of students is in class X TO 2 with an average percentage score of 42.25%, while the lowest level of environmental literacy is obtained in class The highest score for the environmental literacy indicator is the basics of ecology with an average score of 51, while the lowest average score is 31 for the environmental concern indicator.